Philosophy and systematic thinking of artificial intelligence technology - Zhihong WANG; Zhen YANG (Dianxin kexue)
Artificial intelligence (AI) technology is considered as a new generation of technological revolution that has received universal attention.The previous scientific and technological revolutions in history have brought about changes in the process of human civilization and further affected the entire social division of labor and international structure.However,due to the nature of artificial intelligence technology itself,its historical significance is quite different from previous scientific and technological revolutions,and it may be the fundamental technology that humanity has crossed over to the free kingdom.In the process of the full penetration and integration of artificial intelligence into the real economy,there are still several key issues that have not been resolved.From the perspective of philosophy and system science,several core issues that in order to get artificial intelligence technology be fully applied in the economic system were analyzed.Finally,some relevant suggestions combined with the China Telecom’s work on AI were given.